Design and fabrication of automatic recycle bin / Muhammad Iqbal Wafiuddin Johar and Raja Muhammad Aslam Raja Arif - Johar, Muhammad Iqbal Wafiuddin; Raja Arif, Raja Muhammad Aslam (School of Mechanical Engineering, 2023)
The improper sorting of recyclable waste leads to environmental pollution, which can be harmful to living organisms. The objective of this project is to develop an automatic recyclable bin that will sort waste accurately into their respective categories, without the need for manual sorting. The bin comprises of sensors to detect each type of waste and containers for each category. A separator mechanism, controlled by servo motors, separates the waste into their respective containers. This automatic recyclable bin is a cost-effective and eco-friendly solution to reduce pollution and minimize the need for producing new items with the same materials. The project will help to raise awareness about the importance of recycling and create a healthier environment for living beings. In conclusion, the automatic recyclable bin project is a sustainable and efficient way to sort waste into their respective categories. It promotes eco-friendliness and encourages responsible waste management, making it an essential project in creating a healthier environment for living organisms.